Preoperative predictors that impact the survival and outcome of patients undergoing secondary cytoreduction for ovarian cancer. (3rd April 2018) - Katsnelson, Marina; Hwang, Wei-Ting; Tahirovic, Emin; Rubin, Stephen C.; Tanyi, Janos L.
Abstract: This study aimed to examine the factors affecting feasibility of optimal and complete secondary cytoreductive surgery (SCRS) and to characterise the prognostic factors that correlate with improved survival in patients who underwent SCRS. This is a retrospective single-institutional cohort study of patients who underwent SCRS for recurrent epithelial ovarian cancer (EOC). One hundred and forty-eight patients met inclusion criteria. Platinum sensitivity was associated with complete cytoreduction at SCRS. Factors associated with suboptimal cytoreduction (SOC) were age >55 years, serous histology, largest tumour implant size >4 cm, and SOC at primary surgery. Overall survival analysis showed significantly longer survival with complete cytoreduction compared to optimal and SOC. Surgical outcome of SCRS was an independent predictor of survival regardless of the outcome of primary cytoreduction. Location of the largest implant, DFI and timing of chemotherapy also impact on survival.